Distribution and Determinants of Peripapillary Retinal Nerve Fiber Layer Thickness and Its Association with Sleep Quality in Chinese Teenagers - Chen-Wei Pan; Yu-Xi Qian; Hua Zhong; Jun Li; Qin Chen (Journal of Ophthalmology)
Purpose. We aimed to evaluate the distribution and determinants of peripapillary retinal nerve fiber layer (pRNFL) thickness and its associations with general sleep quality in Chinese school students. Methods. 1063 grade 7 students aged 13 to 14 years with pRNFL thickness data from a school-based study on grade 7 students in Southwestern China participated in the study. The pRNFL thickness was measured on the optical coherence tomography images of a circular scan centered on the optic disc. Refractive error was measured after cycloplegia using an autorefractor and biometric parameters including axial length (AL) were measured by an IOLMaster. Participants’ sleep quality was measured by the Children’s Sleep Habits Questionnaire (CSHQ). Results. The mean pRNFL thickness was 106.8 ± 10.7 μm among the 1063 participants. There was an increasing trend of spherical equivalent and a decreasing trend of AL with RNFL thickness. In multivariate analysis, each diopter of spherical equivalent increase was associated with 0.64 μm increase in pRNFL thickness. Girls had an increased mean pRNFL thickness compared with boys with a mean difference of 1.65 μm. Per 10 μm increase in pRNFL thickness was significantly associated with a 0.5 reduction in CSHQ score (better sleep quality). Conclusions. More myopic refractive error was the major ocular determinant of decreased pRNFL thickness. In addition, students with thinner pRNFL tended to have a worse sleep quality.